Exploring Foundation Phase pre-service teachers' mathematical pedagogical content knowledge for teaching additive mental mathematics strategies - Kumm, Marisa Luisa (Rhodes University, Faculty of Education, Department of Primary and Early Childhood Education)
Poor learner performance in mathematics remains a concern in South African primary and secondary education according to continuous national and international assessments. Many learners fall behind in the early grades without being provided the opportunity to establish a solid foundational number sense. This is an essential requirement to progress into the higher grades. Addressing the challenges of number sense in the Foundation Phase is mandatory. This study aimed to investigate third-year Foundation Phase pre-service teachers' content knowledge and pedagogical content knowledge of their additive reasoning strategies (a key aspect of number sense) at a private teacher education institution, guided by the question: What content knowledge and pedagogical content knowledge do third-year Foundation Phase pre-service teachers have of additive reasoning mental mathematics strategies? Several researchers have identified the need to develop pre-service teachers' mathematical content knowledge and pedagogical content knowledge. This study was guided by Shulman's (1986) constructs of teacher knowledge. This qualitative, descriptive study, which formed part of the Mental Mathematics "“ Work Integrated Learning (MM-WIL) programme, collected data from an interpretivist perspective. The information for this study was gathered from participants who agreed to be part of the study. The study collected data through pre- and post-intervention questionnaires that had two parts. The first part assessed pre-service teachers' methods of solving four basic additive reasoning calculations (that lent themselves to using the strategies of bridging through ten, jump strategy, and rounding and adjusting). The second part of the questionnaire asked pre-service teachers to describe these strategies and how they would teach them, with the aim of understanding their additive reasoning skills and ability to use and teach these mental strategies. Key findings are that many pre-service teachers do not have the content knowledge to solve basic calculations using efficient methods. These are skills that they are required to teach in the Foundation Phase classroom. The findings in this study highlight the urgent need to address the weak content knowledge, pedagogical content knowledge and inefficient unit based counting methods of many pre-service teachers to improve learners' development and fundamental understanding of numbers that allows for flexible and efficient calculation.
Keywords: Pedagogical content knowledge; Mathematics-- Study and teaching (Primary) -- South Africa; Pre-service teacher education; Student teachers -- South Africa; Addition-- Study and teaching (Elementary); Number concept-- Study and teaching (Elementary)